Efficacy of holmium laser enucleation of the prostate (HoLEP) in men with bladder outlet obstruction (BOO) and non‐neurogenic bladder dysfunction. Issue 9 (13th July 2017) - Pyun, Jong Hyun; Kang, Sung Gu; Kang, Seok Ho; Cheon, Jun; Kim, Je Jong; Lee, Jeong Gu
Abstract: We aimed to compare the short‐term outcomes of men who had urodynamic evidence of detrusor underactivity (DU) or detrusor overactivity (DO) of a non‐neurogenic etiology as well as bladder outlet obstruction (BOO) and who underwent Holmium Laser Enucleation of the prostate (HoLEP). A database of 322 patients who underwent HoLEP between 2010 and 2014 was analyzed. Patients were classified into three groups according to the results of a preoperative urodynamic study. Preoperative parameters such as International Prostate Symptom Score (IPSS), Quality of Life (QoL) index, IPSS grade, uroflowmetry were compared with postoperative parameters measured at 6 months. There were 138 patients with BOO‐only and 89 patients with BOO and detrusor dysfunction including 56 with DO and 33 with DU. The degree of improvement in IPSS‐total (BOO: 10.7, DO: 8.3, DU: 7.0; p = 0.023) was greater in the BOO‐only group than in the DU group. There were more patients whose IPSS grade improved in the BOO‐only group (71%) than in the detrusor dysfunction group (DO: 53.6% and DU: 45.5%). Postoperative IPSS‐voiding (4.5 vs 7.0), and Qmax (18 vs 13.7) in the BOO‐only group were significantly better than those in the DU group. Additionally, postoperative IPSS‐storage (4.7 vs 6.7), and IPSS‐total (9.1 vs 12.3) in the BOO‐only group were significantly better than in the DO group (all p < 0.05). In conclusion, early surgical management for men with severe LUTS and associated BPH before secondary degeneration occurs may be beneficial for preserving detrusor function and yield better treatment outcomes.